Analysis of Voluntary National Reports in Africa: Morocco, Senegal, Ethiopia and Namibia - Díaz Lafuente, José (Revista Española de Desarrollo y Cooperación, 2020)
This article pursues the analysis of the implementation of the SDG in the African continent through the comparative study of the Voluntary National Reviews (VNR) presented by Morocco, Senegal, Ethiopia and Namibia. To that extent, it presents a critical analysis of the degree of institutionalization of the 2030 Agenda, the progress and challenges in complying with the SDGs, the data collection, evaluation and monitoring systems of the implementation of the SDGs and of the mechanisms and processes of communication and citizen participation.
Keywords: SDG; 2030 Agenda; Africa; Voluntary National Reviews